BREAST CANCER AND IN VITRO FERTILIZATION PROGRAM - A. A. Parokonnaya; M. I. Nechushkin; Ye. B. Kampova-Polevaya; L. N. Lyubchenko (Опухоли женской репродуктивной системы)
Eleven cases of breast cancer (BC) diagnosed during or after in-vitro fertilization (IVF) are considered. The study group was observed to have cases of familial BC in 18.2% of the patients and BRCA1 gene mutations in 60%. At the same time 45.5% of cases had local- ly advanced and generalized BC, which suggests that there is a tumor at the initiation of a regular IVF cycle. The authors arrive at the conclusion that it is necessary to include a mammologist's examination, breast ultrasonography, and an oncogeneticist's counseling into the package of compulsory measures during IVF.